In high Spinal Block of apnoea is secondary to hypotension but not primary for respiratory muscle paralysis Experience in Rajshahi Medical Collage Hospital - Alam, Md Intakhab; Rahman, Md Lutfor; Haque, Md Ekramul; Jesmin, Shahela (TAJ: Journal of Teachers Association, 2009)
This experience was based on ten cases of caesarean section. After spinal anesthesia within few minutes-these patients become cyanosed and there was profound bradycardia and hypotension. Ventilatory support was given by IPPV and I/V bolus vasopressor was given. The BP was improved spontaneous respiration returns. The artificial ventilatory support was with drawn again. So artificial ventilation was reinstituted and vasopressor was given both intermittently and as infusion. The patient began to take spontaneous respiration and the blood pressure became static. There was no further fall of BP and no further deterioration of respiration. doi: 10.3329/taj.v20i2.3077 TAJ 2007; 20(2): 144-146